(untitled) (Prilozi za orijentalnu filologiju, 2019)
Ḥasan Ibn Muṣṭafa Busnawi al-Madani (17th century) is one of the prominent authors of older Bosniak literature in Oriental languages. Although known primarily as a scholar in the field of hadith studies, he also left behind a significant number of works of prose and poetry in Arabic. This paper presents the qasidas included in his diwan, which give an immense contribution to the literary heritage of older Bosnian literature in Oriental languages. An analysis of these qasidas using the synergy of several literary-theoretical approaches, including aesthetic, literary-historical, moral-didactic, religious and other criteria relevant for the inner world of the qasida, will try to provide a contribution to further valuation of the poetic output of this author in the Oriental-Islamic literature as a vast inter-literary and inter-textual system.